The association of female masturbation with self-esteem, body image and sexual satisfaction - Indíana Rós Ægisdóttir 1992- (2016)
The current study was conducted to examine the association between masturbation and relationship status with self-esteem, sexual satisfaction and body image in young women. The study analyzed data from an online self-report anonymous questionnaire. Participants were 99 female students aged 20 – 25 years old (M = 22.93). Participants were all in the Psychology and the Sports Sciences Departments at Reykjavík University. The study was approved by the National Bioethics Committee and the Privacy and Data Protection Authority in Iceland. Results revealed that the majority of participants masturbated regularly. A two-way independent ANOVA was used for statistical analysis. Results revealed that there was no significant main effect between relationship status or masturbation and self-esteem and body image. Results indicated however, a significant main effect for both masturbation and relationship status with sexual satisfaction, indicating that participants who were in a relationship had significantly higher levels of sexual satisfaction than participants who were single. Likewise, participants who masturbated regularly had significantly higher levels of sexual satisfaction than those who do not masturbate regularly. There was not a significant interaction between masturbation or relationship status and self-esteem, sexual satisfaction or body image. Keywords: Young women, masturbation, self-esteem, sexual satisfaction, body image. Rannsókn þessi var framkvæmd til að athuga tengsl á milli sjálfsfróunnar og sambandsstöðu við sjálfstrausts, kynlífsánægju og líkamsímynd hjá ungum konum. Rannsóknin skoðaði gögn sem fengin voru úr nafnlausri netkönnun. Þátttakendur voru 99 kvenkyns nemendur á aldrinum 20-25 ára (M = 22.93). Þátttakendur voru allir nemendur bæði í sálfræði og íþróttafræðideild Háskólans í Reykjavík. Rannsóknin var tilkynnt til Persónuverndar og fékk leyfi Vísindasiðanefndar. Tvíhliða fervikagreining var notuð fyrir tölfræðilega greiningu. Niðurstöður rannsókninnar sýndu að það voru hvorki marktæk ...